Dysregulated Class I histone deacetylases are indicators of poor prognosis in multiple myeloma - Mithraprabhu, Sridurga; Kalff, Anna; Chow, Annie; Khong, Tiffany; Spencer, Andrew (Epigenetics, 2014)
Histone deacetylases (HDAC) control gene expression through their ability to acetylate proteins, thereby influencing a diverse range of cellular functions. Class I HDAC (HDAC1-3 and 8) and HDAC6 are predominantly upregulated in malignancies and their altered expression in some cancers has a significant prognostic implication. The expression and prognostic consequence of dysregulated Class I HDAC and HDAC6, key players in multiple myeloma (MM), are unknown. This study hypothesized that HDAC are dysregulated in MM and patients with high expression have significantly poorer prognostic outcomes. Quantitative PCR for 11 HDAC (Class I, II, and IV) was performed in genetically heterogeneous human myeloma cell lines (HMCL) and primary MM and compared to normal plasma cells (PC). In HMCL, HDAC1-3 and 8 (Class I), and HDAC5 and HDAC10 (Class II) were significantly upregulated compared to normal PC. In primary MM, the median expression level of all of the HDAC, except HDAC1 and HDAC11, were elevated when compared to normal PC. Patients with higher levels of HDAC1-3, HDAC4, HDAC6, and HDAC11 transcripts demonstrated a significantly shorter progression-free survival (PFS). Immunohistochemical staining for HDAC1 and HDAC6 on bone marrow trephines from a uniformly treated cohort of transplant eligible MM patients revealed that HDAC1 protein was detectable in most patients and that higher levels of MM cell HDAC1 protein expression (≥90 % versus ≤20 % MM cell positivity) correlated with both shorter PFS (P = 0 .07) and shorter overall survival (P = 0 .003). Conversely, while the majority of patients expressed HDAC6, there was no correlation between HDAC6 levels and patient outcome. Together, these results indicate that overexpression of Class I HDAC, particularly HDAC1, is associated with poor prognosis in MM.